Evaluation on Students’ Achievement for Outcome Based Education on Engineering Students - Hasan, Hanapi; Ambiyar, Ambiyar; Rizal, Fahmi; Maksum, Hasan; Putri, Tansa Trisna Astono (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2024)
This article explores the implementation and impact of Outcome-Based Education (OBE) in engineering programs, emphasizing the shift from traditional methods to focusing on students' higher-order thinking and practical skills. It highlights how various educational standards, such as those from Engineers Australia and ABET, align with OBE principles. Using an anonymous online survey, the study evaluates the Program Educational Objectives (PEOs) achievement among graduates from the Mechanical Engineering Education Department at Universitas Negeri Medan. The survey covers graduates' skills in areas like mathematical tools, 3D modeling, and engineering project execution. Results indicate that while some PEOs are satisfactorily achieved, others, such as PEO3 (3D modeling skills) and PEO7 (experimental approaches), require improvement. The study suggests enhancing curriculum components to better align with industry needs and continuously improve educational quality. Future research should incorporate employer feedback to provide a more comprehensive evaluation of graduates' preparedness.